2010
DOI: 10.1186/1471-2407-10-697
|View full text |Cite
|
Sign up to set email alerts
|

Separate and combined analysis of successive dependent outcomes after breast-conservation surgery: recurrence, metastases, second cancer and death

Abstract: BackgroundIn the setting of recurrent events, research studies commonly count only the first occurrence of an outcome in a subject. However this approach does not correctly reflect the natural history of the disease. The objective is to jointly identify prognostic factors associated with locoregional recurrences (LRR), contralateral breast cancer, distant metastases (DM), other primary cancer than breast and breast cancer death and to evaluate the correlation between these events.MethodsPatients (n = 919) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
3
6
0
Order By: Relevance
“…In a study of the survival time of MPMN, second primary small-cell lung cancer (SCLC) was compared with first primary SCLC, and no significant differences were found in efficacy and median survival time. 27,28…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of the survival time of MPMN, second primary small-cell lung cancer (SCLC) was compared with first primary SCLC, and no significant differences were found in efficacy and median survival time. 27,28…”
Section: Resultsmentioning
confidence: 99%
“…In a study of the survival time of MPMN, second primary small-cell lung cancer (SCLC) was compared with first primary SCLC, and no significant differences were found in efficacy and median survival time. 27,28 Although there is not yet a consensus of prognostic factors of MPMN, several studies have shown consistent prognostic factors, including the MPMN occurrence interval, earlier or later stage of the disease and tumor type, biological characteristics, and whether or not diagnosis and correct treatment are applied in a timely manner, including radical surgery, adjuvant chemotherapy, and radiotherapy. The definition of SMPMN and MMPMN is the starting point to achieve accurate comparisons, and 6 months is the standard criterion used in most previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism might be associated with chemotherapy drug-induced DNA-protein crosslinkages and/or DNA strand breaks and cell transformations, mutations, and chromosomal aberrations (Noronha et al, 2006). Patients with malignant tumors generally receive long-term chemicals for anticancer treatment and high-dose hormone therapy, resulting in decreased immune function, thus making them more prone to cancer (Rondeau et al, 2010). Immune reconstitution after systemic chemotherapy is not only important for the prevention of cancer recurrence and metastasis, but is also an important measure for the prevention of the occurrence of multiple primary cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Distant metastases at diagnosis are more frequently seen in patients with large tumors or axillary lymph node metastases [7,8]. Therefore, it is standard practice to perform a search for distant disease prior to an intensive treatment regime with curative intent [9,10].…”
Section: Introductionmentioning
confidence: 99%